Prevalence of dementia in Nigeria: a systematic review of the evidence - Davies Adeloye; Asa Auta; Martinsixtus Ezejimofor; Ayo Oyedokun; Michael O Harhay; Igor Rudan; Kit Yee Chan (Journal of Global Health Reports)
# Background